Religiosity Competitiveness on Knowledge Conversion:A New Approach to Boost Adaptive Selling Capability - Sudarti, Ken; Fachrunnisa, Olivia (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2020)
A very dynamic market conditions and the diversity of customers’ character in the financial services industry requires companies to be able to adjust selling methods according to the conditions encountered. In the knowledge management perspective, the wealth and variety of knowledge possessed by salespersons are determinants of adaptive selling capability which will ultimately contribute to the growth of the financial services industry. Various studies have tried to explore the leverage factors of adaptive selling, but not much studies who used perspective of knowledge conversion activities based on personal values as approach. Thus, this study offers a new concept, namely Religiosity Competitiveness on Knowledge Conversion (RCKC) and examines its impact on adaptive selling capability. The study was conducted on 157 Sharia insurance salespersons by taking samples using purposive sampling technique. The test results show that RCKC which compose of religiosity competitiveness on socialization, religiosity competitiveness on externalization, religiosity competitiveness on combination and religiosity competitiveness on internalization can increase adaptive selling capability. Thus, the ability to convert knowledge about good sales techniques as a result of the religiosity competitiveness will increase adaptive selling capability. This in-depth study is expected to contribute to knowledge management practices and policies, especially in knowledge conversion.